Evaluating the use of proactive surveillance and remote patient monitoring to guide the timing of valve intervention in patients with severe asymptomatic aortic stenosis (APRAISE-AS): results of a pilot randomised controlled trial - Nazish Khan; Richard P Steeds; Samir Mehta; Yongzhong Sun; Derek Kyte; Larissa Fabritz; Phil Collis; Clive Stubbs; Mary Nulty; James M Cotton (Heart, 2026)
Background The insidious nature of aortic stenosis (AS) combined with the advanced age of the affected population results in underreporting of symptoms and underestimation of impact on functional capacity and quality of life. Although guidelines recommend early valve replacement in severe asymptomatic AS when coupled with adverse prognostic features, capacity within healthcare systems may limit translation into clinical practice. The use of remote monitoring and proactive surveillance to inform clinical management of heart valve disease is an underexplored area. APRAISE-AS evaluated the utility of remote monitoring to pre-empt/detect a change in clinical status (incorporating a symptom tracker, frailty assessment and quality of life score) to inform patient management. Methods 12-month open-label, two-arm, parallel group randomised controlled pilot trial conducted in two tertiary cardiac centres. 38/66 participants (≥18 years) with asymptomatic severe AS were randomly assigned (1:1) to standard care or the APRAISE-AS intervention in addition to standard care. The primary aim of the study was to (1) test the trial protocol, (2) determine acceptability of the APRAISE-AS intervention and (3) inform the most appropriate outcome measure(s) and sample size for a full-scale randomised controlled trial. Results 38 participants were assigned to standard care (n=19) or to standard care plus the APRAISE-AS intervention (n=19). Adherence rates were high: 81% for the weekly symptom assessments, 91% for the fortnightly timed up and go tests and 93% for the monthly health-related quality of life assessments using the Kansas City Cardiomyopathy Questionnaire (KCCQ). Clinical review and onward referral for valve replacement were triggered by a change from baseline in symptoms and KCCQ scores. Conclusion Remote monitoring of severe asymptomatic AS can be safely delivered in practice. Although the pilot did not recruit to target, a digitally enabled clinical pathway to optimise the management of asymptomatic severe AS is acceptable to clinicians and patients. Trial registration number ISRCTN19413194 .